2014
DOI: 10.1111/een.12128
|View full text |Cite
|
Sign up to set email alerts
|

Priority effects on the life‐history traits of two carrion blow fly (Diptera, Calliphoridae) species

Abstract: 1. Third instars of the invasive blow fly Chrysomya rufifacies are facultative predators on larvae of the native blow fly Cochliomyia macellaria.2. The effects of priority arrival time on the survivorship and fitness of C. rufifacies and C. macellaria were investigated in laboratory experiments.3. Cochliomyia macellaria colonising a resource within 1-2 days after C. rufifacies resulted in a 20-70% reduction in survivorship, pupal weight and fecundity compared with those colonising a resource more than 2 days b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 59 publications
0
34
0
Order By: Relevance
“…Research has also explored species interactions among carrion arthropods ranging from competition (Goodbrod and Goff ), niche partitioning (Denno and Cothran ), predator–prey interactions (Brundage et al. ), and trophic cascades responsible for variability in succession trajectories (Pechal et al. ).…”
Section: The Necrobiomementioning
confidence: 99%
“…Research has also explored species interactions among carrion arthropods ranging from competition (Goodbrod and Goff ), niche partitioning (Denno and Cothran ), predator–prey interactions (Brundage et al. ), and trophic cascades responsible for variability in succession trajectories (Pechal et al. ).…”
Section: The Necrobiomementioning
confidence: 99%
“…Though first instars feed solely on decaying animal tissues, second and third instars also engage in facultative predation and cannibalism (Chitnis, 1965;Wells & Greenberg, 1992a, 1992b though these previous studies relied exclusively on observations under laboratory conditions. Some of the potential ecological ramifications of this predatory behavior in invasive territories include driving the local extinction of native fauna, altering attraction and colonization patterns of carrion by other blow flies (Brundage, Benbow, & Tomberlin, 2014;Spindola, Zheng, Tomberlin, & Thyssen, 2016), and changing the predation patterns of beetle species (Wells & Greenberg, 1992a). Therefore, work with C. rufifacies presents an opportunity to study the ecological impact and molecular regulation of a complex behavior in an invasive species.…”
mentioning
confidence: 99%
“…Furthermore, Brundage et al . () observed that when C. macellaria larvae arrived 2 days after C. rufifacies, they exhibited the most dramatic decrease in survivorship, pupal weight, and adult longevity of all treatments.…”
Section: Discussionmentioning
confidence: 93%
“…However, Brundage et al . () demonstrated that C. rufifacies had greater fitness when colonising a resource concurrently with C. macellaria , suggesting that a predator–prey relationship between those species might impact the dynamics of carrion colonisation as strongly as competition for food (Brundage et al ., ). In this respect our results confirm previous studies on the same competition model (Wells & Greenberg, ), in which a deleterious effect of C. rufifacies on C. macellaria populations was observed across a range of densities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation